The Influence Of Tangibel, Empathy, Responsiveness, Reliability, Assurance On Customer Satisfaction (Case Study Faruqalkan Wedding Organizer) - Suryani, Irma; Naruliza, Esty; Ermeila, Sri (Jurnal Fokus Manajemen, 2024)
This study aims to analyze the effect of Tangible, Empathy, Responsiveness, Reliability, and Assurance variables on the level of customer satisfaction at FaruqAlkan Wedding Organizer located in Palembang City, this type of research is qualitative analysis, the sample used in this study was 24 people with saturated side taking, The data analysis technique used in this study is multiple linear regression analysis, and the results of this study use a validity test which is declared valid because each question RHitung above RTabel (0.4404). The reliability test is declared reliable because each question Crobach's alpha is above 0.60. The t test (partial) stated that the variables Tangible, Empathy, Responsiveness, Reliability, and Assurance have a significant effect on the Consumer Satisfaction variable. The F test (simultaneous) states that the variables Tangible, Empathy, Responsiveness, Reliability, and Assurance together or simultaneously have a significant effect on Customer Satisfaction.The results of the analysis indicate the influence of the variables Tangible, Empathy, Responsiveness, Reliability, and Assurance which are able to explain consumer satisfaction by 86.8%. Meanwhile, the remaining 13.2% is influenced by other factors outside the variables studied, such as Product Quality, Price, and Emotional Factors.